MANAJEMEN PENDIDIKAN ANAK USIA DINI - Rohmat Rohmat (Yinyang: Jurnal Studi Islam Gender dan Anak, 2017)
Abstract: Early childhood education management aims to make the organization’s management work well. One of the indicators of good early childhood education management is to provide effective services for early childhood education. The things above greatly affect the performance of early childhood education services. In its development, pragmatic aspects such as competition, institutional imaging and the like, became the decisive factors in the management of early childhood education institutions. As a result, many early childhood educational institutions no longer function in accordance with their objectives.In early childhood education management has a service orientation in the form of health and nutrition services, growth, intelligence and psychological services, social services and attitudes (Emotional), religious services and spiritualization. It aims at early childhood to have learning experience, optimal developing brain, healthy physical growth, and positive psychosocial development. The substance of early childhood education management includes: the competence of educators, the pattern of coaching, development, and dismissal of educators and education as well as human resource management.Keywords: Education management, early age Abstrak: Manajemen pendidikan anak usia dini bertujuan agar penggelolaan lembaga dapat berlangsung dengan baik. Salah satu indikator manajemen pendidikan anak usia dini yang baik adalah dapat memberikan pelayanan yang efektif bagi pendidikan anak usia dini. Halhal tersebut diatas sangat mempengaruhi kinerja pelayanan pendidikan anak usia dini. Dalam perkembangannya, aspek-aspek pragmatis seperti persaingan, pencitraan lembaga dan sejenisnya, menjadi faktor-faktor penentu dalam manajemen lembaga pendidikan anak usia dini. Akibatnya, banyak lembaga pendidikan anak usia dini tidak lagi berfungsi sesuai dengan tujuan pendiriannya.Dalam manajemen pendidikan anak usia dini mempunyai orientasi layanan berupa layanan kesehatan dan gizi, pertumbuhan, layanan kecerdasan dan psikologis, layanan sosial dan sikap (Emosional), layanan keagamaan dan spiritualisasi. Hal ini bertujuan agar anak usia dini memiliki pengalaman belajar, otak berkembang optimal, pertumbuhan fisik sehat, dan perkembangan psikososial positif. Substansi manajemen pendidikan anak usia dini meliputi : kompetensi pendidik, pola pembinaan, pengembangan, dan pemberhentian tenaga pendidik dan kependidikan serta manajemen sumber daya manusia.Kata Kunci: Manajemen pendidikan, usia dini